DEVELOPMENT OF SOCIAL STUDIES LEARNING THROUGH ROLE PLAYING GAMIFICATION ASSISTED BY PUPPET MEDIA TO INCREASE COLLABORATIVE STUDENTS OF CLASS 7G UM LABORATORY JUNIOR HIGH SCHOOL - Sari, Erna; Kurniawan, Bayu; Rahayu, Linda Zulkifa; Wati, Arista; Choiroh, Dista Ayu Umdatul (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This article proposes an innovative approach by combining gamification, role-playing, and puppet media to increase student engagement in group discussions in social studies learning. The Design Thinking method used shows a systematic framework for designing and developing effective learning media. However, this article could have made clearer the challenges faced during implementation and how to overcome them. Although the pilot test results showed significant improvement, the article could have further analyzed the impact of this method on students’ understanding of the material. Overall, this article makes a good contribution to the development of learning strategies that are interactive and relevant to the needs of today’s students.